EXPLORERS OF THE COLDEST PLACES ON EARTH - Yomtov, Nelson (North Mankato, Minnesota : Capstone Press, 2021)
Of all the places to explore on Earth, remote places are often said to be the most challenging. Yet brave explorers travel to the most remote corners of the world, pushing through vast forests, icy polar regions, and other landscapes. Who are these adventurers and why do they do it?
t Felicity Aston -- t t
Juvenile audience
Keywords: Explorers -- Juvenile literature; Volcanoes -- Juvenile literature; Caves -- Juvenile literature; Juvenile works; Juvenile literature